First Description of Non-Enzymatic Radical-Generating Mechanisms Adopted by Fomitiporia mediterranea: An Unexplored Pathway of the White Rot Agent of the Esca Complex of Diseases - Samuele Moretti; Mary-Lorène Goddard; Alessandro Puca; Jacques Lalevée; Stefano Di Marco; Laura Mugnai; Eric Gelhaye; Barry Goodell; Christophe Bertsch; Sibylle Farine (Journal of Fungi, 2023)
Fomitiporia mediterranea (Fmed) is the primary Basidiomycota species causing white rot in European vineyards affected by the Esca complex of diseases (ECD). In the last few years, an increasing number of studies have highlighted the importance of reconsidering the role of Fmed in ECD etiology, justifying an increase in research interest related to Fmed’s biomolecular pathogenetic mechanisms. In the context of the current re-evaluation of the binary distinction (brown vs. white rot) between biomolecular decay pathways induced by Basidiomycota species, our research aims to investigate the potential for non-enzymatic mechanisms adopted by Fmed, which is typically described as a white rot fungus. Our results demonstrate how, in liquid culture reproducing nutrient restriction conditions often found in wood, Fmed can produce low molecular weight compounds, the hallmark of the non-enzymatic “chelator-mediated Fenton” (CMF) reaction, originally described for brown rot fungi. CMF reactions can redox cycle with ferric iron, generating hydrogen peroxide and ferrous iron, necessary reactants leading to hydroxyl radical (•OH) production. These observations led to the conclusion that a non-enzymatic radical-generating CMF-like mechanism may be utilized by Fmed, potentially together with an enzymatic pool, to contribute to degrading wood constituents; moreover, indicating significant variability between strains.